ANALISIS KELAYAKAN PEMBUKAAN CABANG LABORATORIUM KLINIK KESEHATAN PATRA MEDICA DI KABUPATEN BOYOLALI - Muhamad Haris Maknun; Hartomo Soewardi; Ali Parkhan (Teknoin, 2017)
Boyolali is one of a large city in central Java of Indonesia which its population increases annually by 31%. This city has several health clinic includes antenatal clinics, general clinic and a clinical laboratory. Currently the numbers of clinics to service people are 77 clinics only. In fact, this district still requires on the other of 318 clinics that have an adequate qualification. Therefore it is crucial to establish some new clinics for satisfying the specified requirements by the district government. The purpose of this study is to analyze the feasibility of establishing a new clinical laboratory as an expansion of the existing clinic based on aspects of market, technics and technology, management, financial, legal and environment. Survey was conducted by distributing questioner and interview to a potential stakeholder. Non parametric statistical analysis is done to test some hypotheses at 5% of significant level and 10% of margin of error. The result of this study shows that the establishment of clinic laboratory in Boyolali is feasible according to an analysis of whole aspects.